ANDROID-BASED EVENT INFORMATION APPLICATION IN THE CITY OF MAKASSAR USING LOCATION BASED SERVICE TECHNOLOGY - Andi Ghalib Muh Dziaulhaq (Journal of Information Technology and Its Utilization, 2020)
Android Based Event Information App in Makassar City using Location Based Sevice technology is an application that provides information about event information, especially in the city of Makassar by utilizing the Android platform. This research is based on the background because there are still many people who do not know the information about events that are ongoing or will be held in the city of Makassar. That is due to the lack of information obtained and the lack of a forum to convey information about the spread of events easily. The purpose of this research is to build an event information application to help the public receive event information quickly and easily, to help people find the route to the event they want with the help of Location-Based Service technology with use of the android platform to convey event information so that it can be accessed whenever and wherever they want. This research produces an Android-based Event Information Application that helping people get event information with 70% testing results and making it easier for people to find routes to the event location according to their wishes by using technology Location-Based Service with a percentage of 60% strongly agrees.